Characterization of Physicochemical and Functional Attributes of Purple Corn (Zea mays L. var. ceratina) Flour and Its Application in Gluten-Free Noodle Development - Ayuningtyas, Laksmi Putri; Hidrotunnisa, Hidrotunnisa; Livianinda Elza, Aldila (Jurnal Pangan dan Agroindustri, 2026)
Gluten-free noodles are increasingly important as alternatives to wheat-based products for consumers with gluten intolerance and for the diversification of functional foods. This study aimed to characterize the physicochemical and functional properties of purple corn flour and evaluate its application in gluten-free noodle development using modified cassava flour (mocaf). Purple corn flour was produced by drying and milling and formulated into noodles at different purple corn flour:mocaf ratios (20:80–60:40). Proximate composition, functional properties, color, and RVA pasting behavior were analyzed, while noodle quality was evaluated through cooking properties, texture profile, anthocyanin content, and antioxidant activity. Purple corn flour showed a peak viscosity of approximately 1750 cP and moderate setback viscosity (342 cP). Increasing purple corn flour significantly increased anthocyanin content (0.75–5.21 mg/L) and antioxidant activity (33.99–49.21% inhibition), while formulation ratio affected cooking time, cooking loss (1.54–4.66%), and hardness (53.59–132.47 g). These results indicate that purple corn flour is a promising functional ingredient for gluten-free noodles with acceptable technological quality and enhanced bioactive properties.